RETREATMENT OF TEETH FILLED WITH LATERAL COMPACTION TECHNIQUE AND BIOCERAMIC-BASED SEALER - COMPARISON OF TIME NEEDED AND EFFECTIVENESS OF DIFFERENT RETREATMENT TECHNIQUES - Мirela Мarinova-Takorovа; Elka Radeva; Iva Kisyova; Emilia Naseva (Peytchinski Publishing, 2019)
Purpose: The aim of the presented study is to evaluate and compare the time needed and the effectiveness of three different retreatment techniques in the removal of root canal filling material from teeth filled with lateral compaction technique and bioceramic-based sealer. Material and methods: Thirty-three extracted single rooted human teeth were used. Roots were enlarged using ProTaper Universal files up to size F2. Teeth were randomly assigned into three groups (n=11), according to the retreatment method: Gr1 - retreated using ProTaper Universal Retreatment files; Gr2 - hand instruments (H files); Gr3 - ultrasonic tips. For determining the effectiveness of the removal of the filling material specimens scanned with CT and then observed under a microscope under 16x magnification. Results: The residual material found in most of the cases was a sealer. Best removal of root canal filling in the coronal and apical part was achieved using the ultrasonic tips and the hand instruments, the difference between the two methods being statistically insignificant. There was no significant difference, concerning the middle part. Conclusions: Complete removal of filling material was not achieved in any part of the root canal. The tested techniques were comparably effective in removal of laterally compacted gutta-percha and bioceramic-based sealer.